BIOSECURITY FOR THE UPLAND GAMEBIRD PRODUCER - Farmer, Emily (My University, 2019)
Biosecurity practices are an important epidemiologic method for any producer to implement. Having sound practices in place can help significantly reduce the risk of disease transmission and incurring death loss in a producer’s flock. Avian Influenza can not only devastate a producer, but also greatly impact the U.S. and global economies. Interventions such as placing footbaths in front of each entrance to a building or pen on the property, proper disposal of dead animals, prompt picking up of spilled feed, and proper litter management all contribute to the health of the animals and success of a producer. Highly Pathogenic Avian Influenza causes very sudden death in the infected bird populations. Not only is this a loss to the producer, but on large scales can also be an incredible loss to the country’s bird populations and the U.S. economy. The 2014-2015 outbreak resulted in the death of millions of birds, a strained trading relationship with our trading partners, and an economic loss in the United States and globally. With the help of the United States Department of Agriculture Animal and Plant Health Inspection Service, Veterinary Services, as well as the Kansas Department of Agriculture, Kansas upland gamebird producers were provided with the tools necessary to prevent disease from entering their farm, as well as a plan should disease make its way into their flocks. Biosecurity plans specific for each producer were created and given to the producers in hard copy and electronic forms for easy editing. In addition, each producer received a generic biosecurity template, the National Poultry Improvement Plan (NPIP) guidelines and audit form, and an introduction letter that explained everything provided to them and how to use it.
Keywords: biosecurity; gamebirds; poultry; Avian Influenza; USDA